2010
DOI: 10.1098/rspb.2010.0163
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effects of floral scent in an insect–plant interaction

Abstract: In southwestern USA, the jimsonweed Datura wrightii and the nocturnal moth Manduca sexta form a pollinator-plant and herbivore-plant association. Because the floral scent is probably important in mediating this interaction, we investigated the floral volatiles that might attract M. sexta for feeding and oviposition. We found that flower volatiles increase oviposition and include small amounts of both enantiomers of linalool, a common component of the scent of hawkmoth-pollinated flowers. Because (þ)-linalool i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 48 publications
0
84
1
Order By: Relevance
“…That phenotypic selection on scent was stronger than for other corolla characters, such as floral color and size in P. digitalis, which was particularly interesting for two reasons. First, because pollinators frequently show consistent color preferences, floral color is generally hypothesized to be adaptive and a likely the insect potentially allows for alternate ecological functions of the enantiomers 18 and, thus, differential natural selection on the two compounds. Therefore, to better understand how linalool might function in P. digitalis, we used a chiral column (Cyclosil-B, Agilent-J&W GC columns) to analyze its optical characteristics.…”
Section: Natural Selection On Floral Volatile Production In Penstemonmentioning
confidence: 99%
“…That phenotypic selection on scent was stronger than for other corolla characters, such as floral color and size in P. digitalis, which was particularly interesting for two reasons. First, because pollinators frequently show consistent color preferences, floral color is generally hypothesized to be adaptive and a likely the insect potentially allows for alternate ecological functions of the enantiomers 18 and, thus, differential natural selection on the two compounds. Therefore, to better understand how linalool might function in P. digitalis, we used a chiral column (Cyclosil-B, Agilent-J&W GC columns) to analyze its optical characteristics.…”
Section: Natural Selection On Floral Volatile Production In Penstemonmentioning
confidence: 99%
“…At high concentrations, linalool can be toxic to a variety of insect species (Abdelgaleil et al, 2009;Chang et al, 2009;Phillips et al, 2010), affecting mortality, growth, activity and feeding in lepidopteran larvae (Rajwinder et al, 2010;Singh et al, 2009). This volatile occurs naturally in two isomeric forms, and a recent study using artificial odour blends has suggested that the R and S isomers of linalool may be perceived differently by the moth Manduca sexta, with both isomers being attractive to nectar feeding moths, but only the R isomer deterring ovipositing moths (Reisenman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Ref. 29 reported that VOC blends with higher levels of (-)-isomer deterred oviposition on Datura wrightii by Manduca sexta moths. More recently, ref.…”
Section: Resultsmentioning
confidence: 99%